2005
DOI: 10.1523/jneurosci.4346-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-3: A Novel Signaling Proteinase from Apoptotic Neuronal Cells That Activates Microglia

Abstract: Microglial activation and inflammation are associated with progressive neuronal apoptosis in neurodegenerative human brain disorders. We sought to investigate molecular signaling mechanisms that govern activation of microglia in apoptotic neuronal degeneration. We report here that the active form of matrix metalloproteinase-3 (MMP-3) was released into the serum-deprived media (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(221 citation statements)
references
References 61 publications
7
212
0
2
Order By: Relevance
“…It has been reported that MMP-3 plays critical roles in dopaminergic neurodegeneration in experimental models of PD both intracellularly, by mediating apoptosis of dopaminergic neurons, and extracellularly by triggering neuroinflammation (Kim et al 2005, Choi et al 2008. Specifically, active form of MMP-3 is released from dopaminergic neuronal cells that are under cellular stress and undergoing apoptosis and leads to microglial activation and production of pro-inflammatory and neurotoxic molecules in microglia and further enhances dopaminergic cell death (Kim et al 2005(Kim et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that MMP-3 plays critical roles in dopaminergic neurodegeneration in experimental models of PD both intracellularly, by mediating apoptosis of dopaminergic neurons, and extracellularly by triggering neuroinflammation (Kim et al 2005, Choi et al 2008. Specifically, active form of MMP-3 is released from dopaminergic neuronal cells that are under cellular stress and undergoing apoptosis and leads to microglial activation and production of pro-inflammatory and neurotoxic molecules in microglia and further enhances dopaminergic cell death (Kim et al 2005(Kim et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, active form of MMP-3 is released from dopaminergic neuronal cells that are under cellular stress and undergoing apoptosis and leads to microglial activation and production of pro-inflammatory and neurotoxic molecules in microglia and further enhances dopaminergic cell death (Kim et al 2005(Kim et al , 2007. Furthermore, nigrostriatal dopaminergic neurodegeneration, microglial activation, and superoxide generation were substantially attenuated in MMP-3 K/K mice exposed to MPTP (Kim et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that Mmp3 is up-regulated in the hippocampus of KA-treated mice (Penkowa et al 2005), and Mmp3 is known to play an important role in dopaminergic neuronal cell death and neuroinflammation (Kim et al 2005. Therefore, we performed immunohistochemistry and RT-PCR to investigate the effect of ghrelin on KA-induced Mmp3 expression in the hippocampus.…”
Section: Ghrelin Attenuates Ka-induced Mmp3 Expressionmentioning
confidence: 97%
“…Some of them are from neurons and others are from pathogens, immune cells or microglia (abd-el-Basset and Fedoroff, 1995;Tsirka, 1997;Suzumura et al, 1998;Tan et al, 1999a;Aloisi et al, 1999b;Moller et al, 2000;Kim et al, 2005). LPS, an endotoxin from the gram-negative bacterial cell wall, is a potent immunostimulant (abdel-Basset and Fedoroff, 1995).…”
Section: Molecules Involved In Microglial Activation and Signal Transmentioning
confidence: 99%